2022
DOI: 10.3389/fimmu.2022.825806
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case of Epstein-Barr Virus-Associated Acute Liver Failure Requiring Hematopoietic Cell Transplantation After Emergent Liver Transplantation

Abstract: Hepatic manifestations of Epstein-Barr virus (EBV) infection are relatively common, mild, and self-limiting. Although fulminant hepatic failure has been reported in a few cases, the contributing factors are unclear. This report discusses a pediatric case of EBV-associated acute liver failure that required urgent liver transplantation; however, liver damage continued to progress post-liver replacement. Monoclonal CD8+ T cells that preferentially infiltrated the native and transplanted liver were positive for EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…3 EBV-ALF can affect both immunocompetent and immunocompromised individuals and is fatal in the majority or requires liver transplantation. 3,4,[7][8][9] The index case depicted the uncommon occurrence of EBV-ALF in an immunocompetent individual with relevant clinical and detailed histopathological features at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…3 EBV-ALF can affect both immunocompetent and immunocompromised individuals and is fatal in the majority or requires liver transplantation. 3,4,[7][8][9] The index case depicted the uncommon occurrence of EBV-ALF in an immunocompetent individual with relevant clinical and detailed histopathological features at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant-related HLH. HLH has been described in the context o HSCT (171,172) and, more rarely, in kidney (124,165) and liver (173)(174)(175) transplant recipients. Post-transplant HLH (PT-HLH) might be triggered by a combination of tissue damage, immunosuppressive therapy (176), alloimmune response, residual malignancies or by infections (171).…”
Section: Mas-hlhmentioning
confidence: 99%
“…18 There are very few studies reporting LT for EBVinduced ALF in children. [54][55][56] Nakazawa et al 56 summarizing the experience from a single center in Japan reported that 11% (5/44) of ALF over a period of 8 y in previously healthy and immunocompetent children was caused by EBV; 3 of the patients needed urgent LT. In the same report, authors reviewed the literature for the LT for EBV-induced ALF and compiled a total of 6 pediatric patients.…”
Section: Epvmentioning
confidence: 99%